2016
DOI: 10.1039/c5mh00259a
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric micromachines with wirelessly controlled navigation and functionality

Abstract: A magnetoelectric micromachine manipulated by magnetic field for both locomotion and on-demand function triggering enlighten the concept of unisource-powered microdevices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 53 publications
1
55
0
Order By: Relevance
“…39,44 Here, the Au coated Ni-nanotubes filled with Chi were immersed in DI water and magnetic fields were applied. In our proposed multifunctional drug delivery system, targeted locomotion is accomplished due to the ferromagnetic properties of the Ni carrier.…”
Section: Resultsmentioning
confidence: 99%
“…39,44 Here, the Au coated Ni-nanotubes filled with Chi were immersed in DI water and magnetic fields were applied. In our proposed multifunctional drug delivery system, targeted locomotion is accomplished due to the ferromagnetic properties of the Ni carrier.…”
Section: Resultsmentioning
confidence: 99%
“…Material demonstrations of such particulate micromachines include core-shell nanoparticles composed of ferromagnetic and magnetostrictive FeGa cores surrounded by ferroelectric and piezoelectric polymeric shells [31], piezoelectric polymeric matrices containing magnetic nanoparticles [32,33], and ceramic ferrimagnetic CoFe 2 O 4 / ferroelectric BaTiO 3 composite nanoparticles [34,35]. Mouse tests have shown that the latter can be magnetically guided across the blood-brain barrier, and that they do not cause toxicity or behavioral impairment [36], suggesting promise in treating traumatic neuronal injuries or degenerative diseases via delivery of drugs or neural progenitor cells and through cell stimulation [31].…”
Section: B Bio-medical Applications: Magnetic-field Control Of Electmentioning
confidence: 99%
“…For example, Chen et al recently developed Janus micromachines, which were halfcoated with CoFe2O4. The magnetically anisotropic coating allowed for the rolling motion of the Janus micromachines on a surface under rotating magnetic fields [76].…”
Section: Chatzipirpiridis Et Al Fabricated Such Structures By Electrmentioning
confidence: 99%